The metabolic score for visceral fat and risk of peripheral arterial disease in hypertension patients: a prospective cohort study - Li, Shiping; Yan, Congcong; Wu, Meihui; Wang, Tao; Zhu, Lingjuan; Yu, Chao; Zhang, Weifang; Zhou, Wei; Bao, Huihui; Cheng, Xiaoshu (Frontiers in Endocrinology, 2026)
BackgroundThe Metabolic Score for Visceral Fat (METS - VF), a novel metric for evaluating visceral adipose tissue, has been demonstrated to exhibit a significant correlation with an elevated cardiovascular risk. Nevertheless, its relationship with peripheral artery disease (PAD) remains ambiguous. Consequently, the present study aimed to explore the association between METS-VF and PAD.Methods and resultsThis prospective study was based on a Chinese H-type hypertension cohort, comprising 6,452 patients. The association between METS-VF and PAD was evaluated using the Cox proportional hazards regression analysis and the method of restricted cubic splines (RCS). During an median follow-up time of 3.9 years, 266 PAD events occurred. The mean age of all participants was 63.20 ± 8.38 years. In the fully adjusted model, each 1-unit increase of METS-VF raised the risk of PAD by 21.0% (HR = 1.21, 95%CI: 1.07, 1.37). There was a saturation effect of METS-VF with an inflection point of 8.63 on PAD. For METS-VF < 8.63, each unit increase was associated with a 69.0% higher risk of PAD (HR=1.69, 95%CI: 1.32–2.16), while for METS-VF ≥8.63, there was no significant association between them (HR=0.93, 95%CI: 0.73–1.19) (P for log-likelihood ratio test= 0.002). Subgroup analysis further showed a significant interaction between METS-VF and current smoking status (P for interaction<0.05), with a stronger association observed in non-smokers.ConclusionMETS-VF exhibited a saturation effect on PAD in hypertensive adults in China. Increased METS-VF was positively associated with a higher risk of PAD among hypertensive adults with METS-VF < 8.63, and this association was more pronounced in non-smokers.